2016
DOI: 10.1155/2016/7097612
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetic Propofol-Induced Gene Expression Changes in Patients Undergoing Coronary Artery Bypass Graft Surgery Based on Dynamical Differential Coexpression Network Analysis

Abstract: We aimed to determine the influence of anesthetic propofol on gene expression in patients treated by coronary artery bypass graft (CABG) surgery based on differential coexpression network (DCN) and to further reveal the novel mechanisms of the cardioprotective effects of propofol. Firstly, we constructed the DCN for disease condition based on Pearson correlation coefficient (PCC) and weight value. Secondly, the inference of modules was applied to search modules from DCN with same members but varied connectivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…Propofol and sevoflurane are widely used in GA, and both have been reported to modulate gene expression [1214]. Culley et al first demonstrated that altered gene expression profile in rats induced by GA was associated with persistent changes in hippocampal gene expression, suggesting that recovery of the brain from anaesthesia was considerably slower than generally recognized [15].…”
Section: Discussionmentioning
confidence: 99%
“…Propofol and sevoflurane are widely used in GA, and both have been reported to modulate gene expression [1214]. Culley et al first demonstrated that altered gene expression profile in rats induced by GA was associated with persistent changes in hippocampal gene expression, suggesting that recovery of the brain from anaesthesia was considerably slower than generally recognized [15].…”
Section: Discussionmentioning
confidence: 99%